The Horror of Serenity - Cassandra Holcombe (Journal of Anime and Manga Studies, 2023)
The sublime is a common subject in European literary studies, particularly in Victorian and Romantic period literary scholarship. The Greek writer Longinus proposed the concept in the 1st century in On the Sublime (first printed in 1554), and Edward Burke later popularized it in his work A Philosophical Enquiry into the Origin of our Ideas of the Sublime and Beautiful (1757). The sublime is less discussed in anime studies due to its European origins, but it has a robust history in Japanese literature and philosophy. Recently, scholars have begun discussing its presence in anime. This paper examines European and Japanese definitions of the sublime and then applies the European Romantic definition to Psycho-Pass. Psycho-Pass’s focus on horror, self-knowledge, and European philosophy makes it an ideal subject for examining the sublime in anime. Rikako Oryo is a schoolgirl who murders her classmates and is hunted by the protagonists in one of the show’s side arcs. Her art emphasizes how the sublime's "horror" element can stimulate critical thought and concurs with the Kierkegaardian theory of the sublime. The primary antagonist, Shogo Makishima, represents the more transcendent aspects of the sublime and its role in self-knowledge and identity. After examining Rikako and Makishima, the paper takes a step back and apply the principles of the sublime to anime as a medium and Psycho-Pass as a whole. Psycho-Pass reminds viewers that violent media like horror anime and crime stories can use the sublime as a catalyst for critical thinking without endorsing violence.